1996
DOI: 10.1093/carcin/17.5.1021
|View full text |Cite
|
Sign up to set email alerts
|

Environmental air pollution and DNA adducts in Copenhagen bus drivers—Effect of GSTM1 and NAT2 genotypes on adduct levels

Abstract: The lymphocyte bulky PAH-DNA adduct levels have been studied in persons occupationally exposed to ambient air pollution. The exposure group consisted of 90 healthy, nonsmoking bus drivers from the Copenhagen area, divided into three exposure groups according to driving area, and 60 rural controls (smokers and non-smokers). PAH-DNA adducts were determined by 32P-postlabelling with the butanol enrichment procedure. The bus drivers answered a comprehensive questionnaire on passive smoking, residential area, diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 38 publications
2
47
2
4
Order By: Relevance
“…An alternative explanation is that highly modified albumin from highly exposed bus drivers could easily be recognized by proteases and degraded. In animal (12). In this study, the negative correlation between albumin and bulky carcinogen-DNA adduct level seen in the combined group was only statistically significant in the GSTM1 null group.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…An alternative explanation is that highly modified albumin from highly exposed bus drivers could easily be recognized by proteases and degraded. In animal (12). In this study, the negative correlation between albumin and bulky carcinogen-DNA adduct level seen in the combined group was only statistically significant in the GSTM1 null group.…”
Section: Discussioncontrasting
confidence: 45%
“…A large interindividual variation in the biomarker levels could be seen. A significant higher level of bulky carcinogen-DNA adducts (12) was observed in the group dassified as the high exposure group, whereas the levels of PAH-albumin adduct and markers of oxidative stress, MDA and AAS, in hemoglobin were significantly higher in the suburban/semirural group. The level of the biomarkers in the postal worker group was similar to the levels in the suburban/semirural bus driver group (Table 1).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…5,6 Several studies have reported higher levels of DNA adducts among subjects heavily exposed to air pollutants, such as police officers, bus drivers, news vendors and residents in heavily polluted areas. [7][8][9] A recent meta-analysis of 13 32 P-DNA postlabeling studies on occupational cohorts has shown that the association between DNA adducts and air pollution exposure is significant in heavily exposed industrial workers and in less severely exposed urban workers. 10 Bulky DNA adducts, such as those induced by PAH, may be repaired by base excision repair (BER) and nucleotide excision repair (NER) pathways.…”
mentioning
confidence: 99%